Biogas upgrading and CO2 capture by adsorption technologies - Silva, José A.C. (2016)
The reduction of CO2 and CH4 emissions to atmosphere is a matter of great concern nowadays since both gases can contribute significantly to the so-called greenhouse effect that describes the trapping of heat near earth´s surface by gases in the atmosphere. At the same time CO2/CH4 separations are of interest in treating gas streams like landfill gas, biogas and coal-bed methane.. Accordingly, there is a need to investigate on this topic and that can be done with improved efficient technologies to separate or remove CO2 and CH4 from exhaust gases.